2014
DOI: 10.1051/0004-6361/201322118
|View full text |Cite
|
Sign up to set email alerts
|

VLT observations of the asymmetric Etched Hourglass Nebula, MyCn 18

Abstract: Context. The mechanisms that form extreme bipolar planetary nebulae remain unclear. Aims. The physical properties, structure, and dynamics of the bipolar planetary nebula, MyCn 18, are investigated in detail with the aim of understanding the shaping mechanism and evolutionary history of this object. Methods. VLT infrared images, VLT ISAAC infrared spectra, and long-slit optical Echelle spectra are used to investigate MyCn 18. Morpho-kinematic modelling was used to firmly constrain the structure and kinematics … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 64 publications
3
36
0
Order By: Relevance
“…Uncertainties in each radial velocity measurement are 1σ uncertainties determined from the standard error in the fit centroid provided by the fitting routine. The average nebular radial velocity of −72.78 ± 0.10 km s −1 agrees well with −71 km s −1 measured from spatio-kinematic modeling (Clyne et al 2014).
Figure 3.The observed N iii λ4634.14 Å profiles (black lines) were fit with a model composed of a Voigt function and a straight line (red lines).
…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Uncertainties in each radial velocity measurement are 1σ uncertainties determined from the standard error in the fit centroid provided by the fitting routine. The average nebular radial velocity of −72.78 ± 0.10 km s −1 agrees well with −71 km s −1 measured from spatio-kinematic modeling (Clyne et al 2014).
Figure 3.The observed N iii λ4634.14 Å profiles (black lines) were fit with a model composed of a Voigt function and a straight line (red lines).
…”
Section: Discussionsupporting
confidence: 86%
“…Included in our survey is the young planetary nebula MyCn 18 (PN G307.5−04.9, Mayall & Cannon 1940), also known as the Etched Hourglass Nebula. The bipolar appearance of MyCn 18 (Figure 1; Sahai et al 1999) is the result of an eponymous hourglass-shaped nebula inclined 38° to the line of sight (Dayal et al 2000; O’Connor et al 2000; Clyne et al 2014). MyCn 18 exhibits several features for which binary interactions are the preferred formation mechanism, yet no evidence has been found supporting the presence of a binary companion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O'Connor et al (2000), Soker & Kashi (2012) and Clyne et al (2014) suggested the possibility that MyCn 18 might have been a SySt, however, it is clearly placed in the PNe regime of the optical diagnostic diagram (Fig. 7).…”
Section: The Optical Pne Versus Systs Diagrammentioning
confidence: 95%
“…The parameters of the model are then interactively adjusted until a satisfactory solution is obtained (e.g. Akras and Steffen 2012;Akras and López 2012;Clyne et al 2014;Clyne et al 2015). Our model of Abell 14 was constructed using the image and kinematic data from the [N ii] λ6584 line due to its lower thermal broadening compared to that of the Hα line (thermal width of the Hα and [N ii] lines at 10,000 K are 21.4 km s −1 and 5.8 km s −1 , respectively).…”
Section: Shape Modellingmentioning
confidence: 99%